On Strictly Convex Central Configurations of the 2n-Body Problem - Barrabés, E.; Cors, J. M. (Journal of dynamics and differential equations, 2019)
We consider planar central configurations of the Newtonian 2 n -body problem consisting in two twisted regular n -gons of equal masses. We prove the conjecture that for n ≥ 5 all convex central configurations of two twisted regular n -gons are strictly convex.